1994
DOI: 10.1007/bf01923476
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth stimulation by inoculation with symbiotic and associative rhizosphere microorganisms

Abstract: Abstract. Selected Rhizobium bacteria, arbuscular mycorrhiza-forming (AM) fungi and associative bacteria have been shown to stimulate the growth of legumes, gramineae and cruciferae in field experiments on different soil types in temperate regions. A combination of microorganisms with different metabolic capacities (N2-fixation, P-mobilization; production of phytohormones and antibiotics) can partly surpass the effect of single inoculations, or can produce a positive effect where single inoculations are ineffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(60 citation statements)
references
References 46 publications
0
58
0
2
Order By: Relevance
“…Furthermore, the soil type, growth stage, cropping practices (such as tillage and crop rotation), and other environmental factors (8,14,20,22,27,52) seem to influence the composition of the microbial community in the rhizosphere. Rhizosphere microorganisms exert strong effects on plant growth and health by nutrient solubilization, N 2 fixation, or the production of plant hormones (19,36). Increased plant productivity also results from the suppression of deleterious microorganisms by antagonistic bacteria, while soil-borne pathogens can greatly reduce plant growth.…”
mentioning
confidence: 99%
“…Furthermore, the soil type, growth stage, cropping practices (such as tillage and crop rotation), and other environmental factors (8,14,20,22,27,52) seem to influence the composition of the microbial community in the rhizosphere. Rhizosphere microorganisms exert strong effects on plant growth and health by nutrient solubilization, N 2 fixation, or the production of plant hormones (19,36). Increased plant productivity also results from the suppression of deleterious microorganisms by antagonistic bacteria, while soil-borne pathogens can greatly reduce plant growth.…”
mentioning
confidence: 99%
“…Mangroves also harbor microorganisms that are important in nutrient cycling (31,40). Many species of terrestrial plants influence microbial communities inhabiting their roots; this phenomenon is known as the rhizosphere effect (33,39). Microorganisms in turn are essential for plant growth and organic matter turnover, and they use plant root exudates as a nutrient source (39,70).…”
mentioning
confidence: 99%
“…Many species of terrestrial plants influence microbial communities inhabiting their roots; this phenomenon is known as the rhizosphere effect (33,39). Microorganisms in turn are essential for plant growth and organic matter turnover, and they use plant root exudates as a nutrient source (39,70). Little is known, however, about the impact of mangrove plants on microbial rhizosphere communities (31,32,72).…”
mentioning
confidence: 99%
“…Van Berkum and Bohlool (1980) reported that diazotrophic bacteria in the rhizosphere utilise the products of nitrogen fixation for their own growth but do not release it while they are alive, the other reason could be the production of phytohormone in the rhizosphere by the microorganisms . Also P. agglomerans and A. chroococcum were able to produce phytohormones in pure culture (Scholz-Seidel and Ruppel 1992, Höflich et al 1994, Pathak et al 1995, Kumar and Narula 1999.…”
Section: Plant Weight and Nutrient Uptake Under Hydroponic Conditionsmentioning
confidence: 99%